Delayed Vision Loss Post Assault-Induced Zygomatic Fracture Repair in a Patient with an Ipsilateral Anterior Clinoid Process Pneumatization, A Case Report - M. Gutierrez Elleny; A. Shaukat Bilal; P. Langford Marlyn; J Brinkley John; A. Byrd William (Journal of Ophthalmic Science, 2023)
A 27-year-old male presented one week after surgical repair of his fractured left zygomatic arch, 5 weeks post-assault, complaining of persistent blurred vision in the left eye and worsening migraine headaches. Magnetic resonance images (MRI) revealed no intra-orbital pathologies or optic neuropathy but demonstrated a clearly delineated air-filled space of the left anterior clinoid process (ACP). No vision threatening pathologies were identified and surgical treatment was not recommended. His blurred vision remained at 6-month follow up. We report a case of delayed vision loss and headache post zygomatic fracture repair surgery in patient with a confirmed ipsilateral ACP pneumatization.
Keywords: air-filled cavity